Comparison of neutrophil lymphocyte ratio (NLR), mean platelet volume (MPV) and platelet lymphocyte ratio (PLR) in preeclampsia and normotensive pregnancies - Dinar Yudistira Firdaus; Assangga Guyansyah; Umiyanti Thenu; Selvia D. Denggo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
The study aimed to compare the NLR (neutrophil lymphocyte ratio), MPV (meanplatelet volume), and PLR (platelet lymphocyte ratio) values in preeclampsiaand normotensive pregnancies. This was a retrospective case-control studyusing medical records of pregnancies between January 1, – December 31, 2019.A total 31 pregnancies with preeclampsia who met the inclusion and exclusioncriteria were involved in the study. As control, 31 normotensive pregnanciesrecruited by simple random sampling were used. The data were presented asmean ± standard deviation (SD) and analyzed by using SPSS program. Receiveroperating characteristic (ROC) curve were used to determine the optimal cutoff point for predicting preeclampsia. The NLR and MPV values of patients withpreeclampsia were significantly higher compare to normotensive pregnancy(p<0.001). Whereas, the PLR value of both groups was not significantlydifferent (p>0.245). The result of AUC analysis showed that the NLR and MPVhave AUC values of 0.758 (95%CI:0.637-0.878; p=0.000) and 0.903 (95%CI:0.816-0.989; p=0.000), respectively. Further analysis showed that the optimal cut-offpoint for NLR was 4.0 (sensitivity of 64.5% and a specificity of 71.0%) and forMPV was 7.55 (sensitivity of 87.1% and specificity of 80.0%). In conclusion, theNLR and MPV values are significantly higher in preeclampsia. However, theMPV value has a better predictive value than NLR for preeclampsia.